The Maximum Caliber principle applied to continuous systems. (May 2016) - González, Diego; Davis, Sergio
Abstract: We give a brief presentation of the maximization of path entropy (Maximum Caliber) formalism as an approach to inference over trajectories. We develop its continuoustime version involving path integrals and present an identity between expectations over the most unbiased probability distribution of trajectories. This relation between expectations can be used to solve for the Lagrange multipliers in a Maximum Caliber problem without the need for the dynamical partition function.